2021
DOI: 10.1111/tpj.15102
|View full text |Cite
|
Sign up to set email alerts
|

Plant apocarotenoids: from retrograde signaling to interspecific communication

Abstract: Summary Carotenoids are isoprenoid compounds synthesized by all photosynthetic and some non‐photosynthetic organisms. They are essential for photosynthesis and contribute to many other aspects of a plant's life. The oxidative breakdown of carotenoids gives rise to the formation of a diverse family of essential metabolites called apocarotenoids. This metabolic process either takes place spontaneously through reactive oxygen species or is catalyzed by enzymes generally belonging to the CAROTENOID CLEAVAGE DIOXYG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
135
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 249 publications
(376 reference statements)
0
135
0
Order By: Relevance
“…Strigolactones are involved in the symbiotic relation between land plants and soil arbuscular mycorrhiza and function as endogenous plant hormones (Moreno et al, 2021). In land plants, CYP711As (also known as MAX1) oxygenate the intermediate carlactone in strigolactone biosynthesis (Abe et al, 2014;Zhang et al, 2014Zhang et al, , 2018Yoneyama et al, 2018;Mori et al, 2020).…”
Section: Cyp Families With Recently Elucidated Functionalitiesmentioning
confidence: 99%
“…Strigolactones are involved in the symbiotic relation between land plants and soil arbuscular mycorrhiza and function as endogenous plant hormones (Moreno et al, 2021). In land plants, CYP711As (also known as MAX1) oxygenate the intermediate carlactone in strigolactone biosynthesis (Abe et al, 2014;Zhang et al, 2014Zhang et al, , 2018Yoneyama et al, 2018;Mori et al, 2020).…”
Section: Cyp Families With Recently Elucidated Functionalitiesmentioning
confidence: 99%
“…Alternatively, this metabolic process could take place spontaneously through ROS‐mediated carotenoid decay, as reported for β‐cyclocitral (Ramel et al , 2012). There are indications for the presence of numerous carotene‐derived metabolites, which are presumed to modulate lateral root formation, plastid biogenesis, leaf morphology, and other developmental processes (Moreno et al , 2020). Therefore, the present study revealed diapocarotenoids as candidates for carotene‐derived regulatory metabolites that modulate plant growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Among the growth and agronomic traits altered by ccd4 and/or pll mutations, mutations in the A or B subgenome homoeologs of CCD4 and PLL alone already had a significant impact on the convex hull area of seminal roots, the seminal root length (1)(2)(3)(4)(5), and the coleoptile length; these mutant phenotypes were exacerbated in ccd-A4 ccd-B4 pll-A pll-B where both A and B subgenome homoeologs were knocked out (Figures 5, 6). This suggests that the A and B subgenome homoeologs of CCD4 and/or PLL play distinct roles in controlling the above-mentioned traits.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, efforts have been directed toward enhancing the production of provitamin A carotenoids, particularly β-carotene, in wheat grains through breeding and biotechnology for improved vitamin A nutrition ( 2 ). However, provitamin A carotenoids produced in wheat grains may be subjected to degradation by carotenoid cleavage dioxygenases (CCDs) that cleave carotenoids (C 40 ) into smaller apocarotenoid molecules ( 3 ). Therefore, it is imperative to better understand the activity and function of CCDs in wheat grains for achieving a high level of provitamin A carotenoid accumulation.…”
Section: Introductionmentioning
confidence: 99%